Classical identification: A viable road for data to inform structural modeling - Roger Hammersland (Statistics Norway, Research Department, 2008)
This paper addresses how to enhance the role of data in structural model design by utilizing structural breaks and superfluous information as auxiliary tools of exact identification. To illustrate the procedure and to study the simultaneous interplay between financial variables and the real side of the economy a simultaneous equation model is constructed on Norwegian aggregate data. In this model, while innovations to stock prices and credit do cause short run movements in real activity, such innovations do not precede real economy movements in the long run.
Keywords: C30; C32; C50; C51; C53; C53; E44; 330; Structural vector Error Correction modeling; Identification; Cointegration; Financial variables and the real economy.